IMPLEMENTATION OF CASCADE CONTROL IN WATER TURBIDITY LEVEL SETTINGS FOR THE PROCESS CONTROL SYSTEM LEARNING MODULE - Much. Ananda Fikri Alghufroni; Imam Saukani; Denda Dewatama (Jurnal Neutrino: Jurnal Fisika dan Aplikasinya)
Learning media is one of the means needed to achieve the perfect quality of education. In the Process Control System Practicum Laboratory of Malang State Polytechnic, the number of learning module plants is limited.. It is necessary to add a new learning module, therefore a plant is designed about regulating the level of water turbidity. In this plant, a cascade control method is used to regulate the mixture of clear water and water with high turbidity in order to obtain water with a certain level of turbidity. The results of the application of the cascade control method using the P controller in the inner loop (flow) with a value of K_p=155 obtained rise time 3s, settling time 4s, and steady state error 15%, in the outer loop (turbidity) was also used P controller with a value of K_p=1.67 resulting rise time 14s, settling time 30s, and steady state error 60%. The high steady state error occurs because the plant response of this system has characteristics that were too fast so that the cascade control was unable to overcome the error. In addition, the SEN0189 turbidity sensor with the accuracy of reading the water turbidity value of 10 NTU every 1mV voltage change and easily exposed to noise was also the cause of this system plant to produce a high steady state error.